2013
DOI: 10.5812/hepatmon.7522
|View full text |Cite
|
Sign up to set email alerts
|

Association Between ABCB1 (MDR1) Gene Polymorphism and Unresponsiveness Combined Therapy in Chronic Hepatitis C virus

Abstract: BackgroundTo treat viral infection of chronic hepatitis C (CHC) is a main strategy to prevent progression of liver disease, and cancer. Some patients with CHC have failed to respond to the common antiviral therapy in different populations.ObjectivesIn the current study it was aimed to find out the possible role of multiple drug resistance gene1 (MDR1) in non-responder patients with CHC infection in Turkish population.Patients and MethodsPeripheral blood-EDTA samples were used for total genomic DNA isolation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The results showed similarity in the prevalence of the C allele and the T allele in the population studied, with CT being the most prevalent genotype in these patients. Among the patients with HCV infection who underwent treatment with pegylated interferon-alpha and ribavirin, our findings corroborate the results found by Timucin et al, which also showed a higher frequency for the CT genotype among these patients (25) . Some studies claim that the presence of the T allele generates no response to treatment, however we did not find such an association; furthermore, the presence of this allele is also associated with development of some type of cancers such as hepatocellular carcinoma, prostate cancer, ovarian cancer and others (28) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed similarity in the prevalence of the C allele and the T allele in the population studied, with CT being the most prevalent genotype in these patients. Among the patients with HCV infection who underwent treatment with pegylated interferon-alpha and ribavirin, our findings corroborate the results found by Timucin et al, which also showed a higher frequency for the CT genotype among these patients (25) . Some studies claim that the presence of the T allele generates no response to treatment, however we did not find such an association; furthermore, the presence of this allele is also associated with development of some type of cancers such as hepatocellular carcinoma, prostate cancer, ovarian cancer and others (28) .…”
Section: Discussionsupporting
confidence: 82%
“…The literature reports an association between the C3435T polymorphism of the MDR1 gene and various diseases. Rose et al suggest a regulatory role of MDR1 gene expression in patients with hepatopathies (24) ; other studies about this SNP have shown that the C allele is associated with a better prognosis in patients with hepatitis C and in patients with hepatocellular carcinoma (1,25) . On the other hand, in other pathological conditions such as HIV infection, the T allele appears to confer a better prognosis; HIV-infected patients homozygous for the TT genotype, when treated with HAART, have shown significant increases in CD4 cell count and better response to the treatment of hepatitis C (11,15,29) .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, both genetic variants of ABCG2 rs2, 231,137 (34 G > A) and rs2, 622, 604T (1143 C > T) were associated with the low sorafenib plasma levels and improved clinical outcome [35]. It is worth mentioning that genetic polymorphisms of both ABCB1 and ABCG2 in relevance to HCC susceptibility, HCC risk of recurrence following liver transplantation [53] as well as a therapeutic response [58] have been thoroughly studied which provide a solid ground for how genetic variability can implicate HCC since its incidence till therapeutic response.…”
Section: Abc Transportersmentioning
confidence: 66%
“…23,24,26,29 It has been reported that C3435T, one of the silent polymorphisms, may be associated with ribavirin resistance in chronic hepatitis C infection. 30 In our study, we investigated whether another silent polymorphism, C1236 T, was associated with lamivudine resistance in chronic hepatitis B patients. The CT genotype (72.5%) was higher in the lamivudineresponsive group in comparison to the non-responsive group (53.8%), however, no statistical difference was noted.…”
Section: Discussionmentioning
confidence: 99%